Analysis on Productivity, Performance and Upward Mobility of Faculty Members - Amoin, Marvin P. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research’s main objective was to decide if the mobility of faculty indeed increases the efficiency and productivity of faculty in terms of teaching, research, and extension. A descriptive research design was implemented in the analysis. Faculty members with a professorial rank based on the National Budget Circular Period assessment were regarded as the study respondents. In terms of main outcome areas, the table of indicators per dimension was used in State Universities and Colleges’ leveling instrument. There is a very strong inter-rater agreement with the collected data using Cohen’s Kappa Index for face validity. Using Lawshe’s method and an internal consistency measure of 0.84 using Cronbach Alpha Coefficient, a content validity ratio is calculated for each object. The Pearson product-moment correlation coefficient was used to calculate the strength of a linear relationship between two variables, following the assumptions underlying its use. The researcher uses a significance level denoted by alpha set at 0.05 statistically relevant to assess the level of significance. To determine the shift in faculty efficiency and productivity over time, the rate of change was used. As the rank of the faculty increases, the corresponding salary rise was also observed. Regarding upward mobility over time, faculty members’ success level is increasingly growing in instructional study and extension services. In terms of instructional research and extension resources about upward mobility over time, faculty members’ degree of productivity is lower than the faculty’s performance.